The grid blueprint for a new computing infrastructure - Foster, Ian, 1959-; Kesselman, Carl. (Amsterdam ; Boston : Morgan Kaufmann, 2004)
The Grid is an emerging infrastructure that will fundamentally change the way we think about-and use-computing. The word Grid is used by analogy with the electric power grid, which provides pervasive access to electricity and has had a dramatic impact on human capabilities and society. Many believe that by allowing all components of our information technology infrastructure-computational capabilities, databases, sensors, and people-to be shared flexibly as true collaborative tools the Grid will have a similar transforming effect, allowing new classes of applications to emerge.-From the Preface In 1998, Ian Foster and Carl Kesselman introduced a whole new concept in computing with the first edition of this book. Today there is a broader and deeper understanding of the nature of the opportunities offered by Grid computing and the technologies needed to realize those opportunities. In Grid 2, the editors reveal the revolutionary impact of large-scale resource sharing and virtualization within science and industry, the intimate relationships between organization and resource sharing structures and the new technologies required to enable secure, reliable, and efficient resource sharing on large scale. Foster and Kesselman have once again assembled a team of experts to present an up-to-date view of Grids that reports on real experiences and explains the available technologies and new technologies emerging from labs, companies and standards bodies. Grid 2, like its predecessor, serves as a manifesto, design blueprint, user guide and research agenda for future Grid systems. *30 chapters including more than a dozen completely new chapters. *Web access to 13 unchanged chapters from the first edition. *Three personal essays by influential thinkers on the significance of Grids from the perspectives of infrastructure, industry, and science. *A foundational overview of the central Grid concepts and architectural principles. *Twelve application vignettes showcase working Grids in science, engineering, industry, and commerce. *Detailed discussions of core architecture and services, data and knowledge management, and higher-level tools. *Focused presentations on production Grid deployment, computing platforms, peer-to-peer technologies, and network infrastructures. *Extensive bibliography and glossary.
Grids in context / Larry Smarr -- The scientific imperative / Fran Berman, Tony Hey -- The industrial imperative / Irving Wladawsky-Berger -- Concepts and architecture / Ian Foster, Carl Kesselman -- Predictive maintenance : distributed aircraft engine diagnostics / Jim Austin, Tom Jackson, Martyn Fletcher, Mark Jessop, Peter Cowley, Peter Lobner -- Distributed telepresence : the NEESgrid earthquake engineering collaboratory / Carl Kesselman, Ian Foster, Tom Prudhomme -- Scientific data federation : the World-Wide Telescope / Alexander S. Szalay, Jim Gray -- Medical data federation : the biomedical informatics research network / Mark Ellisman, Steve Peltier -- Knowledge integration : in silico experiments in bioinformatics / Carole Goble, Chris Greenhalgh, Steve Pettifer, Robert Stevens -- Distributed data analysis : federated computing for high-energy physics / Greg Graham, Richard Cavanaugh, Peter Couvares, Alan De Smet, Miron Livny -- Massively distributed computing : virtual screening on a desktop grid / Andrew A. Chien -- Enterprise resource management : applications in research and industry / Wolfgang Gentzsch -- Interactivity with scalability : infrastructure for multiplayer games / David Levine, Mark Wirt -- Service virtualization : infrastructure and applications / Ming Xu, Zhenhua Hu, Weihong Long, Wayne Liu -- Group-oriented collaboration : the access grid collaboration system / Rick Stevens and Futures Lab Group -- Collaborative science : astrophysics requirements and experiences / Gabrielle Allen, Edward Seidel -- The open grid services architecture / Ian Foster, Carl Kesselman, Steven Tuecke -- Resource and service management / Karl Czajkowski, Ian Foster, Carl Kesselman -- Building reliable clients and services / Douglas Thain, Miron Livny -- Instrumentation and monitoring / Jeffrey Hollingsworth, Brian Tierney -- Security for virtual organizations : federating trust and policy domains / Frank Siebenlist, Nataraj Nagaratnam, Von Welch, Clifford Neuman -- Data access, integration, and management / Malcolm Atkinson, Ann L. Chervenak, Peter Kunszt, Inderpal Narang, Norman W. Paton, Dave Pearson, Arie Shoshani, Paul Watson -- Enhancing services and applications with knowledge and semantics / Carole A. Goble, David De Roure, Nigel R. Shadbolt, Alvaro A.A. Fernandes -- Application-level tools / Henri Bal, Henri Casanova, Jack Dongarra, Satoshi Matsuoka -- Languages, compilers, and run-time systems / Ken Kennedy -- Application tuning and adaptation / Daniel A. Reed, Celso L. Mendes, Charng-da Lu -- Production deployment : experiences and recommendations / William E. Johnston, John M. Brooke, Randy Butler, David Foster, Micro Mazzucato -- Computing elements / Andrew A. Chien -- Peer-to-peer technologies / Jon Crowcroft, Tim Moreton, Ian Pratt, Andrew Twigg -- Network infrastructure / Joe Touch, Jon Poste.
Includes bibliographical references (p. [675]-721) and index.
Keywords: Computational grids (Computer systems).; Electronic books